2020
DOI: 10.1371/journal.pone.0238523
|View full text |Cite
|
Sign up to set email alerts
|

Transgene behavior in Zea mays L. crosses across different genetic backgrounds: Segregation patterns, cry1Ab transgene expression, insecticidal protein concentration and bioactivity against insect pests

Abstract: Brazil and South Africa, countries with economies in transition, are characterized by a dual agrarian structure co-occurring, sometimes, alongside in the same region. Large-scale commercial farming produces crops for export to global markets on the one hand, and smallscale farming, on the other hand, provides for subsistence and local markets. In both systems, maize (Zea mays) is a key crop for these two countries. For the commercial system, maize is a commodity crop while for the small-scale system it is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 79 publications
3
15
0
Order By: Relevance
“…Future research will benefit from a note of caution stemming from results presented here: we show here that there is poor or no correlation between the active presence of the cry1Ab transgene, the corresponding levels of mRNA or Bt toxin in leaves, and the insecticidal bioactivity of the toxin. These results are similar to earlier findings in crossing experiments with open-pollinated varieties of maize, instead of teosinte plants [39]. As in those complementary studies, we confirm here again that cry1Ab-derived mRNA is not a good predictor of Cry1Ab concentration or insect mortality.…”
Section: Policy and Management Observationssupporting
confidence: 93%
See 1 more Smart Citation
“…Future research will benefit from a note of caution stemming from results presented here: we show here that there is poor or no correlation between the active presence of the cry1Ab transgene, the corresponding levels of mRNA or Bt toxin in leaves, and the insecticidal bioactivity of the toxin. These results are similar to earlier findings in crossing experiments with open-pollinated varieties of maize, instead of teosinte plants [39]. As in those complementary studies, we confirm here again that cry1Ab-derived mRNA is not a good predictor of Cry1Ab concentration or insect mortality.…”
Section: Policy and Management Observationssupporting
confidence: 93%
“…Overall, as previously observed in experiments with non-GM maize plants (i.e., hybrids and open-pollinated maize varieties, Lohn et al [39]), the mRNA levels of the cry1Ab transgene in the crop-hybrid teosinte plants do not appear to determine directly, in any measurable way, the concentration of the produced Cry1Ab toxin. Based on other studies, the suggestion for such an apparently paradoxical behavior is that there are other plant regulatory processes influencing the final concentration levels of the Cry1Ab toxin, such as post-transcriptional, translational and protein degradation/synthesis regulation [40][41][42][43], or even promoter activity changes that could be influencing in the mRNA level changes [44].…”
Section: Correlation Between Transgene Expression and Cry1ab Concentrationsupporting
confidence: 62%
“…This is due to self-pollination that results in genotypic segregation, in which some plants contained the Glu-1Dx5 transgene, but some did not. This is because that transgene segregation may occur after consecutive self-pollination as reported by for UidA gene (GUS) and cry1Ab transgene Lohn et al 2020). This data confirms that the Glu-1Dx5 transgene has been integrated into the rice genome of cultivar Fatmawati.…”
Section: Molecular Confirmation Of the Glu-1dx5 Transgenesupporting
confidence: 81%
“…Zenner-de-Polanía (2021) [ 37 ] reported that the greatest concern regarding maize transgene flow is a potential damage to the diversity of existing breeds and the accumulation of transgenic DNA. Lonh et al (2020) [ 38 ] observed degeneration of maize landraces in a study carried out in the state of Santa Catarina in the southern region of Brazil, where the transgenic protein Cry1AB was introduced in a landrace to monitor the evolution of gene expression and concentration as well as its effects on the mortality of insects Helicoverpa armigera and Spodoptera littoralis . It was concluded that unintentional crossing between landraces and transgenic varieties causes irreversible damage since gene transcription and insect control bioactivation is stable and reliable.…”
Section: Discussionmentioning
confidence: 99%